Pemberdayaan Usaha Masyarakat Melalui Pelatihan Digitalisasi UMKM Oleh Mahasiswa KKN Kolaboratif UPN “Veteran’ Jawa Timur - Cavine One Happy Panjaitan; Kalvin Edo Wahyudi; Novita Wahyu Ningtias; Fiola Febriani; Gyta Adhelia Putri Sekarwangi (Universitas Negeri Surabaya, 2025)
Increasing skills and marketing access for MSME owners, including Women Headed Families (PEKKA), is very important to improve their welfare. In Menampu Village and Sabrang Village, MSMEs face challenges in business management and marketing digitalization. The